Opening panel: Adult education then and now - Michael Newman (Adult Education Research Conference, 2015)
This is not so much a paper as four quotations from the author’s previous writings, along with some annotations. The author describes his first encounter with adult education. He looks at one of the reasons why adult education was robust. He describes the onset of professionalism. He describes the effects of specialisation. And he identifies the paradoxical situation adult education finds itself in today
Keywords: adult education; specialisation; paradox